Powrót tańczącego ciała na irlandzką scenę w kontekście „niepokornych lat dziewięćdziesiątych” - Ojrzyńska, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
Prompted by the swift economic growth and the equally rapid decline of the authority of the local Catholic Church, the 1990s witnessed a significant change in the Irish attitude towards national culture and morality. One of the fields which best illustrates these transformations is dance, whose new face can be seen as symbolically representing the Irish transition from a country still bearing the stigma of de Valera’s ethical and cultural policies to a more liberal and open-minded European nation. The 1990s are the times of abolishing the taboos imposed years earlier on the Irish body perceived as an object of distrust that needs to be kept under constant surveillance to serve the nationalist cause as an epitome of proper moral conduct. With this in mind, the paper aims to discuss both the nature of the most crucial aspects of the revolution in the Irish dance in the 1990s and the effect this has exerted on the condition of the Irish stage. This will provide substantial background for the discussion of selected recent works of such playwrights as Brian Friel, Vincent Woods or Tom Kilroy, which make extensive use of dance, showing their contribution to challenging the literary, word-based character ofIrish drama and theatre.